The design of radiant floor heating system combind with other types of heating system using solar evacuated tubes - Hoor, Ahmad; Massad, Ahmad; Tamimi, Hazem (جامعة بوليتكنك فلسطين - ميكانيك, 2008)
Using the solar energy is the popular method to decrease global warming that affect on the earth, so we will use this solar energy to produce heating systems to residential place which contains two floors occupied with six persons. The area is about 167m2 american style villa. Using a new technology that absorbs the sun rays better than other collectors which we called solar evacuated tubes heat pipe collector. The project includes the calculation of total load ( heating and domestic hot water ) of the villa (43 kw ) , the radiation of our design month in winter is about 381.5 W/M2 in hebron city , these values lead us to calculate the collector area which is 63 m2 , this value covers only the heating load (23kw) . the maximum actual efficiency of solar heat pipe collector that we reached is about 67% from the sun radiation that collected by the solar heat pipes. By using the (PLC) programmable logic control, we control our system that provide us any information of each components of the system like display the temperatures and know the faults of any parts in it, also the control system serve the users to operate any of the two floors inside the villa.
no of pages 124,22811, ميكانيك 13/2008 , in th estore
Keywords: radiant floor heating; heating systems; solar evacuated tubes